An Optimization Approach for Fault Current Limiter Installation Considering Distributed Generation Impact and Circuit Breaker Constraints - Akin, Firat; Arikan, Oktay (SPRINGER HEIDELBERG, 2026)
The fault current levels in power systems are increasing due to the new power plants and distributed generation units have been installed to meet the growing demand for electrical energy. This situation results in violations of circuit breaker ratings, preventing necessary operations during faults and leading to damage in power system equipment. At this point, fault current limiters (FCLs) serve as an important solution. This study proposes a novel algorithm for determining the size, location, and number of FCLs. Unlike traditional approaches, FCLs are placed not only on transmission lines but also at generator connection points. A modified sensitivity analysis is used to reduce search space of candidate FCL locations. During the optimization process, both resistive and inductive types of FCLs are used, and economic analyses are conducted to identify the cost-effective type. The number, locations, and sizes of FCLs needed to reduce fault currents to the desired levels, considering circuit breaker (CB) ratings and safety margins, are determined in a modified IEEE 30-bus test system with added DG. Finally, the FCL costs are evaluated based on the short-circuit power of connected distributed generation (DG) units.
Keywords: Fault current limiters; Particle swarm optimization; Distributed generation; Sensitivity analysis; Power system reliability; PARETO-OPTIMAL ALLOCATION; PLACEMENT; ALGORITHM; Science & Technology - Other Topics